Are the Physical and Social Capitals Still Productive Resources for Coffee Agroforestry Development?: The Evidence of Endogenous Growth Role in Leveraging the Sluggish Production Factors at Batutegi Forest Management Unit - Bakri, Samsul; Apriliani, Adella Putri; Kaskoyo, Hari; Wulandari, Christine (Jurnal Manajemen Hutan Tropika, 2024)
Increasing income (INC) is a key variable for the encroacher's self-empowerment in order to able to leave protected forest areas voluntarily when their concessionary period will be due. This urgency is facing by almost Social Forestry Programs across the country such as for Batutegi Lampung Province, whose empowerment period only has 20 years left so that they don't become encroachers again. While physical capital (PC), especially forest land, has seemed leveling off for increasing INC, so the stimulating social capital (SC) is a must. In this context, the role of extension activities (ROLE) in amplifying PC and SC productivity in leveraging INC needs to be elucidated. The objectives of this research are to: (1) reveal the strengths of the direct effect of ROLE on INC, (2)compare the effectiveness of ROLE in leveraging SC to PC in order to increase INC, and (3) evaluate the effectiveness of ROLE in stimulating FC and SC in order to leverage INC. The SEM (structural equation modeling) postulates employed at a confidence level of 95%, where PC and SC are treated as exogenous variables, ROLE as intervening variables, and INC as endogenous variables. The land tenure both inside and outside the forest area is used as an indicator for the PC. Elements of norms, trust, and network as indicators for SC. The three indicators for ROLE employed are the benefit of extension activities about forest protection, agroforestry technique, and post-harvest skill. Two indicators for INC are from coffee beans and other non-timber forest products (NTFP). Data collection was carried out in between April to June 2020 through semi-structured interviews with 98 forest encroachers who were drawn using stratified random sampling. Conclusion: (1) FC and SC not directly productive, did not significantly increase INC (P=0.740 and 0.123 respectively), and in contrast to ROLE were highly productive (P=0.000), (2) PC was also not significantly stimulated to ROLE (P=0.112) but SC was significant (P=0.000) and [3] for PC the ROLE activities were blunt or not significant in amplifying INC (P=0.188) but very powerful or significant for SC (P=0.000). The implication: to ensure that encroachers or HKm land concession holders are able to leave protected forest areas voluntarily when their concession rights expire, the FMU authority must increase the knowledge and skills of HKm concession holders through strengthening extension performance (ROLE) as a necessary condition for increasing income, not continuing to increase the land allotment.